How to Compete in the Age of Artificial Intelligence Implementing a Collaborative Human-Machine Strategy for Your Business - Mohanty, Soumendra (Apress, 2018)
Get started with artificial intelligence in your business. This book will help you understand AI, its implications, and how to adopt a strategy that is rational, relevant, and practical. Beyond the buzzwords and the technology complexities, organizations are struggling to understand what AI means for their industry and how they can start their journey. How to Compete in the Age of Artificial Intelligence is not a book about complex formulas or solution architectures. It goes deeper into explaining the meaning and relevance of AI for your business. You will learn how to apply AI thinking across enterprise functions-including disruptive technologies such as IoT, Blockchain, and cloud-and transform your organization. What You'll Learn: Know how to spot AI opportunities and establish the right organizational imperatives to grow your business Understand AI in the context of changing business dynamics and the workforce/skills required to succeed Discover how to apply AI thinking across enterprise functions-from the boardroom to cybersecurity, IoT, IT operations, policies-and implement a sustainable and integrated human-machine collaboration strategy.